(sinx+1)(cosx-2)=0

Simple and best practice solution for (sinx+1)(cosx-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (sinx+1)(cosx-2)=0 equation:


Simplifying
(sinx + 1)(cosx + -2) = 0

Reorder the terms:
(1 + insx)(cosx + -2) = 0

Reorder the terms:
(1 + insx)(-2 + cosx) = 0

Multiply (1 + insx) * (-2 + cosx)
(1(-2 + cosx) + insx(-2 + cosx)) = 0
((-2 * 1 + cosx * 1) + insx(-2 + cosx)) = 0
((-2 + 1cosx) + insx(-2 + cosx)) = 0
(-2 + 1cosx + (-2 * insx + cosx * insx)) = 0

Reorder the terms:
(-2 + 1cosx + (cinos2x2 + -2insx)) = 0
(-2 + 1cosx + (cinos2x2 + -2insx)) = 0

Reorder the terms:
(-2 + cinos2x2 + 1cosx + -2insx) = 0
(-2 + cinos2x2 + 1cosx + -2insx) = 0

Solving
-2 + cinos2x2 + 1cosx + -2insx = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + cinos2x2 + 1cosx + 2 + -2insx = 0 + 2

Reorder the terms:
-2 + 2 + cinos2x2 + 1cosx + -2insx = 0 + 2

Combine like terms: -2 + 2 = 0
0 + cinos2x2 + 1cosx + -2insx = 0 + 2
cinos2x2 + 1cosx + -2insx = 0 + 2

Combine like terms: 0 + 2 = 2
cinos2x2 + 1cosx + -2insx = 2

Add '2insx' to each side of the equation.
cinos2x2 + 1cosx + -2insx + 2insx = 2 + 2insx

Combine like terms: -2insx + 2insx = 0
cinos2x2 + 1cosx + 0 = 2 + 2insx
cinos2x2 + 1cosx = 2 + 2insx

Reorder the terms:
-2 + cinos2x2 + 1cosx + -2insx = 2 + 2insx + -2 + -2insx

Reorder the terms:
-2 + cinos2x2 + 1cosx + -2insx = 2 + -2 + 2insx + -2insx

Combine like terms: 2 + -2 = 0
-2 + cinos2x2 + 1cosx + -2insx = 0 + 2insx + -2insx
-2 + cinos2x2 + 1cosx + -2insx = 2insx + -2insx

Combine like terms: 2insx + -2insx = 0
-2 + cinos2x2 + 1cosx + -2insx = 0

The solution to this equation could not be determined.

See similar equations:

| 3n^2-6n-9=0 | | 0.57=logx | | 3n^2+12n-90=-8 | | k^2-4k-60=0 | | 9x+9y+18=0 | | 6y-3=5-2y | | 7x-14=-7x | | 66-(4x+12)=4(x+9)+x | | 10-5x=2(5x-10) | | 0.03x+0.05(2000-x)=99.5 | | 22x-23Y=21 | | 4=6x-3+7 | | e^5x-1=12 | | 24+5y=9y | | 8x+3(2x-1)=5x+6 | | 22=2w-8 | | 3(x-4)=5(x-6) | | K-9=-11 | | 4x+5(5/2)=15 | | 1-2(x-1)=x+6 | | -12=2+h | | 4(-3)+5y=15 | | -9w+3= | | 3x-5(0)=8 | | 3(1)-5y=8 | | 4x-9y=-15 | | 5+4.5= | | 2x^2-3bx+b^2=0 | | -16t^2+80t+224=0 | | 5+4.5=9 | | -2x+6=5x-2y | | 3x^2+12y=3 |

Equations solver categories